Evaluation of environmental sustainability threshold of “humid” and “dry” building systems, for reduction of embodied carbon (CO2) - Giacomo Di Ruocco; Roberta Melella (Vitruvio: International Journal of Architectural Technology and Sustainability)
The New Italian Procurement Code (Legislative Decree No. 50/2016), in compliance with the EU directives 26/02/2014, has introduced, among other things, the possibility of obtaining awards, during the awarding of the contract , in terms of reducing the estimated energy impact in the life cycle of the work. The objective of this study was to direct architectural design towards conscious choices that are compatible with environmental legislation. The study, therefore, aimed to analyze the characteristics of the most widespread (wet and dry) construction systems, in order to determine environmental sustainability thresholds referring to each of the four systems hypothesized for the development of the model. The simulated cases for the definition of the model refer to the following construction systems: M1 (structural system in load-bearing masonry); M2 (constructive system with frame structure and traditional brick cladding); M3 (constructive system with metallic bearing structure and dry stratified shell); M4 (constructive system with wooden supporting structure and dry stratified shell). The results indicated design scenarios aimed at using constructive systems that present advantages in terms of disassembly, recovery and reuse of the various components; in addition to the attitude of such systems, to be resilient, or to be able to be adapted and transformed during the life cycle of the building organism.